Environmental economics in developing countries : issues and challenges - Acharyya, Achiransu (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The COVID-19 pandemic has laid bare the vulnerabilities of socio-economic systems globally and exposed the risks that natural capital degradation imposes on human health, economy, and society. This book studies the environmental challenges faced by developing economies in a post-COVID-19 world. Exploring diverse case studies from South Asia and Sub-Saharan Africa, the volume discusses the impact that economic development and, recently, COVID-19 has had on the environment, ecology, and economy of these regions. It analyses nature conservation policies aimed at minimizing ecological damage arising from economic development and discusses the policy objectives of sustainable development. It also highlights the significant role that environmental economics networks have played in capacity building, framing of policies using ecological economics tools, and developing a local leadership trained in addressing local sustainability issues. An important contribution to the study of environmental economics of the Global South, the book will be of interest to students and researchers of economics, environment, development studies, development economics, environmental policies, and South Asia studies. It will also be useful for policymakers and NGOs working in this field"--
Keywords: Economic development -- Environmental aspects -- Developing countries; Sustainable development -- Developing countries; Environmental economics -- Developing countries; BUSINESS & ECONOMICS / Environmental Economics; BUSINESS & ECONOMICS / Development / General; POLITICAL SCIENCE / Public Policy / Environmental Policy